Rescher, Nicholas, Collected Papers, Bd. 10: Studies in the History of Logic, Ontos Verlag: Frankfurt a.M. 2006 - Peckhaus, Volker (zbMATH Open, Zbl. 1117.03005)

Anellis, Irving H., “Some Views of Russell and Russell’s Logic by his Early Contemporaries”, Review of Modern Logic 10 (2004/05), 67–97 - Peckhaus, Volker (Mathematical Reviews, MR2238774 (2007d:03002))

De Mol, Liesbeth, “Closing the Circle: An Analysis of Emil Post’s Early Work”, Bulletin of Symbolic Logic 12 (2006), 267–289 - Peckhaus, Volker (Mathematical Reviews, MR 2007a:03002)

Crocco, Gabriella, “Gödel on Concepts”, History and Philosophy of Logic 27 (2006), 171–191 - Peckhaus, Volker (Mathematical Reviews, MR2227083 (2007e:03007))

Actin-dependent regulation of connective tissue growth factor - Muehlich, Susanne; Cicha, Iwona; Garlichs, Christoph D.; Krueger, Bettina; Posern, Guido; Goppelt-Struebe, Margarete (American Journal of Physiology-Cell Physiology)
Expression of connective tissue growth factor (CTGF) in endothelial cells is modulated by shear stress affecting the organization of the cytoskeleton. The molecular connection between alterations of actin and CTGF expression was investigated in human umbilical vein endothelial cells (HUVEC) and a microvascular endothelial cell line. Overexpression of nonpolymerizable monomeric actin R62D interfered with stress fiber formation in HUVEC and concomitantly reduced immunoreactive CTGF. In microvascular endothelial cells, flow-dependent upregulation of CTGF was prevented by this actin mutant. In contrast, overexpression of actin S14C strengthened filamentous actin and increased CTGF expression. These data indicated an inverse relationship between CTGF expression and monomeric actin. Coexpression of the mutant actins and different CTGF promoter constructs revealed an actin-sensitive site between 3 and 4.5 kb of the CTGF promoter. A CArG-like box at -3791 bp was responsible for actin-dependent CTGF induction as shown by mutagenesis. Overexpression of actin S14C activated the nonmutated promoter significantly more strongly than the mutated promoter. Actin polymerization is regulated by the small GTPase RhoA and activation of serum response factor (SRF). Overexpression of constitutively active RhoA or SRF significantly increased CTGF protein synthesis. The 4.5-kb promoter construct, but not the construct with a mutation in the CArG box, was activated by SRF or RhoA, providing evidence for a functional role of this site in CTGF induction. These findings provide novel evidence that monomeric actin is the connecting link between alterations in the cytoskeleton and CTGF gene expression and demonstrate the importance of SRF in regulating CTGF transcription.

Efficient Operation in Sensor and Actor Networks Inspired by Cellular Signaling Cascades - Dressler, Falko; Dietrich, Isabel; German, Reinhard; Krueger, Bettina (1st ACM/ICST International Conference on Autonomic Computing and Communication Systems (Autonomics 2007))
The investigation and the development of self-organizing systems are especially needed for operation and control in massively distributed systems such as Sensor and Actor Networks (SANETs). The main issues addressed by self-organization techniques are scalability, network lifetime, and real-time support. In the literature, biological principles are often cited as inspirations for technical solutions, especially in the domain of self-organization. This concept already resulted in a good number of solutions with significant impact such as ant-based routing and immune system inspired network security solutions. In this paper, another specific biological field is investigated: cellular signaling cascades for event-specific reaction initiated by individual cells in collaboration with their direct neighbors. Information between cells are transmitted via proteins and result in the cascade of protein–protein or protein–DNA interactions to produce a specific cellular answer, e.g. the activation of cells or the transmission of mediators. These processes are programmed in every individual cell and lead to a coordinated reaction on a higher organization platform. We transferred these mechanisms to operation and control in SANETs. In particular, a rule-based processing scheme relying on the main concepts of cellular signaling cascades has been developed. It is relying on simple local rules and providing problem specific reaction such as local actuation control and data manipulation. We describe this Rule-based Sensor Network (RSN) technology and demonstrate comparative simulation results that show the feasibility of our approach.

Adaptive Data Dissemination in Sensor Networks using WPDD - Dressler, Falko; German, Reinhard; Krueger, Bettina (IEEE Frontiers in the Convergence of Bioscience and Information Technologies (FBIT 2007))
In Wireless Sensor Networks (WSNs), address-based routing approaches often lead to severe problems due to node mobility, energy-saving sleep-cycles, and often missing or unreliable address information. Data-centric routing schemes such as flooding or gossiping solve these problems but may lead to congestion or starvation. Based on biologically inspired mechanisms known from cellular signaling pathways, we discovered potentials in enhancing the communication required for self-organization in network environments suffering from data paths with low reliability and time variations of the reliability. Using an importance factor for particular transmissions in combination with feedback loops, the overall quality of the global system can be increased. The resulting algorithm, Weighted Probabilistic Data Dissemination (WPDD), includes an inherent adaptation to changing network conditions. Congestion control is supported as well as prioritized data communication. This paper outlines the working behavior of WPDD and demonstrates its applicability based on selected simulation results.

Storying Domestic Violence: Constructions and Stereotypes of Abuse in the Discourse of General Practitioners - Mildorf, Jarmila

Mad Intertextuality: 'Jane Eyre', 'Wide Sargasso Sea', 'After Mrs Rochester' - Mildorf, Jarmila (A Breath of Fresh Eyre: Intertextual and Intermedial Reworkings of 'Jane Eyre')

“Conversations about Taking our Own Lives – Oh, a Poor Expression for a Forced Deed in Hopeless Circumstances!” - Suicide Among German Jews 1933-1943 - Hartig, Christine (Leo Baeck Institute Yearbook)

Ernst Zermelo. An Approach to His Life and Work - Ebbinghaus, Heinz-Dieter; Peckhaus, Volker
Rezension: Neue Zürcher Zeitung v. 6. Juni 2007 (G. Szpiro); Ralf Bülow, “Hundert Jahre moderne Mathematik”, heise online v. 13.02.2008 (http://www.heise.de/newsticker/Hundert-Jahre-moderne-Mathematik–/meldung/103411); Mathematical Reviews 2007m:01024 (J.M. Plotkin); MAA Online 5. Juli 2007 (M. Berg); Philip J. Davis, “The Z of ZF and ZFC and ZF¬C”, SIAM News 41.1, January/February 2008; SIAM Review 50.1 (2008), 167–169; (J.W. Dawson); European Mathematical Society Newsletter June 2008, 54; The Mathematical Intelligencer 31 (2009), 79–81 (Henry E. Heatherly); Notices of the AMS 56 (2009), 823–827 (G.H. Moore); Zbl. Math. 1176.01001 (H.K. Sørensen).

Balthasar Neumann als fürstbischöflicher Baukommissar - Süßmann, Johannes (Die Kunst der Mächtigen und die Macht der Kunst. Untersuchungen zu Mäzenatentum und Kulturpatronage)

Vergemeinschaftung durch Bauen. Würzburgs Aufbruch unter den Fürstbischöfen aus dem Hause Schönborn - Süßmann, Johannes

Film- und Tonaufnahmen. Träger konservierter Inhalte und modernen Wissens. - Varga, Eva (Anschauungsmaterial. Fachgeschichte als Sachgeschichte.)

T. Denean Sharpley-Whiting's ,Pimps Up, Ho's Down: Hip Hop's Hold on Young Black Women, New York and London: New York University Press, 2007 - Strube, Miriam (Particip@tions: International Journal of Audience Research)

Flippin da script: Supa Sistas und Rap Musik - Strube, Miriam (HipHop Meets Academia: Globale Spuren eines lokalen Kulturphänomens)

Sampling methods for shortest vectors, closest vectors and successive minima - Blömer, Johannes; Naewe, Stefanie (Proceedings of the 34th ICALP)

Reflexive Interkulturalität als Schul(sport)entwicklungs-perspektive - Skizze einer Schulfallstudie an der Laborschule Bielefeld - Grimminger-Seidensticker, Elke; Gieß-Stüber, P.; Schmerbitz, H.; Seidensticker, W. (Standardisierung, Profilierung, Professionalisierung. Herausforderungen für den Schulsport)

Sportpädagogische Herausforderungen durch eine multikulturelle Schülerschaft – Ein Plädoyer für die Ausbildung interkultureller Kompetenz von Sportlehrkräften - Grimminger-Seidensticker, Elke; Gieß-Stüber, P. (Beruf: Sportlehrer/in)

Unter der Geissel Gottes. Das Leiden der stigmatisierten Maria von Mörl (1812–1868) im Urteil ihres Beichtvaters